2018
DOI: 10.1002/pbc.27309
|View full text |Cite
|
Sign up to set email alerts
|

Health‐care providers’ perspectives on traditional and complementary alternative medicine of childhood cancer in Kenya

Abstract: HCP need to improve their knowledge of TCAM and facilitate open communication about TCAM with families so parents feel safe to discuss their interest in it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…A total of 24 studies (Fig. 1) were included in this review [10,18,, n = 16 surveys [10,18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41], n = 5 expert opinions [42][43][44][45][46], and n = 3 qualitative studies [47][48][49].…”
Section: Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 studies (Fig. 1) were included in this review [10,18,, n = 16 surveys [10,18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41], n = 5 expert opinions [42][43][44][45][46], and n = 3 qualitative studies [47][48][49].…”
Section: Searchesmentioning
confidence: 99%
“…Assessment of methodological quality/critical appraisal Five (n = 5) cross-sectional studies were assessed as low risk of bias as they had addressed nine out of nine items in its design, conduct, and analysis [31,34,38,40,41] (see Table 2). Three cross-sectional studies (n = 3) [10,18,28] addressed eight items, six studies (n = 6) [30,32,33,[35][36][37] addressed seven items, one study (n = 1) [29] addressed six items, and one study (n = 1) [39] addressed only four out of nine items.…”
Section: Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…He is trained in qualitative research and had experience in conducting semi-structured interviews among health professionals and patients in Sierra Leone. We developed the interview guide based on the available scholarship on HCPs knowledge, attitude and practice of T&CM as well as their views regarding its integration with conventional medicine [26][27][28][29][30][34][35][36][37][38]. The guide was pretested among three HCPs, and their response helped to inform the design of the final version of the interview guide.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Such T&CM competency requires HCPs to be knowledgeable about commonly used T&CM. However, studies have shown that HCPs are less knowledgeable about T&CM, which limit their ability to provide appropriate advice to their patient regarding T&CM, use [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%